Subspecies and Distribution. P. h. hispida Schreber, 1775 — Arctic Ocean. P h. botnica Gmelin, 1788 — Baltic Sea. P. h. ladogensis Nordqvist, 1889 — Lake Ladoga (W Russia). Ph. ochotensis Pallas, 1811 — Sea of Okhotsk and N Japan (Hokkaido). P. h. saimensis Nordqvist, 1889 — Lake Saimaa (S Finland). in Phocidae - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
Subspecies and Distribution. P. h. hispida Schreber, 1775 — Arctic Ocean. P h. botnica Gmelin, 1788 — Baltic Sea. P. h. ladogensis Nordqvist, 1889 — Lake Ladoga (W Russia). Ph. ochotensis Pallas, 1811 — Sea of Okhotsk and N Japan (Hokkaido). P. h. saimensis Nordqvist, 1889 — Lake Saimaa (S Finland). Published as part of Russell A. Mittermeier & Don E. Wilson, 2014, Phocidae, pp. 120-183 in Handbook of the Mammals of the World – Volume 4 Sea Mammals, Barcelona :Lynx Edicions on page 182, DOI: 10.5281/zenodo.6607185